Mural Sebagai Pendukung Perkembangan Kreativitas Anak di Taman Kanak - Kanak Pertiwi Desa Piruko Timur, Nagari Sitiung - Muhammad Hafrison; Vi Zhilalil Qur’ani; Hasnatul Fadhilah; Muhammad Fadly; Hasrul Hazani; Haikal Julianda Putra (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Creativity is an important aspect of children's development, especially during their golden age of growth. Pertiwi Kindergarten (TK) in East Piruko Village, Nagari Sitiung is one of the agents that contributes to the formation of children's creativity through various approaches, one of which is with mural media. The purpose of this study is to analyze the role of murals in supporting the development of early childhood creativity and its impact on the learning environment. The study uses a qualitative method with a descriptive approach that includes observations, interviews with teachers and parents, and documentation of the mural manufacturing process. The results of the study show that murals are not only a sweetener for the school environment, but also an effective learning medium. It provides visual stimuli that enhance children's imagination and creativity, increase the active participation of teachers, parents and the community, and create a sense of belonging to the school environment. The challenges in implementing murals are budget and deadlines, but these can be overcome through collaboration with the community. Overall, murals at Pertiwi Kindergarten serve as creative learning tools that increase children's motivation and participation in the learning process. This study recommends the use of murals as one of the innovative ways of early childhood education.